2007
DOI: 10.1111/j.1365-2966.2007.11920.x
|View full text |Cite
|
Sign up to set email alerts
|

NGC 2236: a moderately metal-poor open cluster of Hyades-like age located beyond the Perseus spiral arm

Abstract: New CCD photometry in the Washington system C and T1 passbands down to T1∼ 18.5 mag in the field of the northern open cluster NGC 2236 is presented. T1 magnitudes and C−T1 colours for a total of 1162 stars within an area of 13.6 × 13.6 arcmin2 were measured. These CCD data were supplemented with photoelectric CMT1T2 photometry of 13 red giant candidates. The comparison of the cluster (T1, C−T1) colour–magnitude diagram with theoretical isochrones computed for the Washington system yields E(C−T1) = 1.10 ± 0.10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Note, however, that the theoretically computed bluest stage during the He-burning core phase is redder than the observed RGC in the CMD of IC 2140 (Fig. 8), a behaviour previously detected in other studies of Galactic and Magellanic Cloud clusters (e.g., Clariá et al 2007;). The age error was estimated considering the isochrones that encompassed those features best.…”
Section: Ages and Metallicitiessupporting
confidence: 70%
“…Note, however, that the theoretically computed bluest stage during the He-burning core phase is redder than the observed RGC in the CMD of IC 2140 (Fig. 8), a behaviour previously detected in other studies of Galactic and Magellanic Cloud clusters (e.g., Clariá et al 2007;). The age error was estimated considering the isochrones that encompassed those features best.…”
Section: Ages and Metallicitiessupporting
confidence: 70%
“…Photometric systems: Caby (C) DDO (D) Johnson (J) Strömgren (S) Vilnius (V) Washington (W) Literature: [1] Anthony-Twarog & Twarog (2000) [2] Anthony-Twarog & Twarog (2004) [3] Anthony- [4] Anthony-Twarog et al (2005) [5] Anthony-Twarog et al (2006) [6]Bruntt et al (1999) [7]Cameron (1985b) [8]Clariá (1982) [9]Clariá (1985) [10]Clariá & Lapasset (1983) [11]Clariá & Lapasset (1985) [12]Clariá & Lapasset (1986a) [13]Clariá & Lapasset (1986b) [14]Clariá & Lapasset (1989) [15] Claria &Mermilliod (1992) [16]Clariá & Minniti (1988) [17] [18]Clariá et al (1991) [19]Clariá et al (1994) [20]Clariá et al (1996) [21]Clariá et al (1999) [22]Clariá et al (2003) [23]Clariá et al (2005) [24]Clariá et al (2007) [25]Clariá et al (2008) [26]Dawson (1981) [27]Eggen (1983) [28]Geisler & Smith (1984) [29]Geisler et al (1992) [30]Janes (1984) [31]Janes & Smith (1984) [32]Kaluzny & Mazur (1991a) [33]Kaluzny & Mazur (1991b) [34]Kaluzny & Mazur (1991c) [35]Kaluzny & Rucinski (1995) [36]Kyeong et al (2008) [37]Lynga & Wramdemark (1984) [38] McClure et al (1981 [39]Mermilliod et al (2001) [40]Nissen (1980) [41]Nissen (1988) [42]Nissen et al (1987) [43] Noriega-Mendoza & Ruelas-Mayorgo (1997 [44]…”
mentioning
confidence: 99%
“…Our goal is to determine reddenings, distances, ages, and if possible also metallicities for poorly known OCs (or candidates), preferably for those located toward the Galactic centre direction (see, e.g., Marcionni et al 2014, hereafter M14). The Washington photometric system has been widely applied to young, intermediate-age and old clusters in the Galaxy (e.g., Geisler et al 1992;Clariá et al 2007;Piatti et al 2009) and in the Magellanic Clouds (e.g., Geisler et al 2003). Geisler et al (1991) and Geisler and Sarajedini (1999) have demonstrated the pross offered by this system in the study of Galactic and/or extragalactic star clusters.…”
Section: Introductionmentioning
confidence: 99%